2008
DOI: 10.1038/npp.2008.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Risperidone on Procedural Learning in Antipsychotic-Naive First-Episode Schizophrenia

Abstract: Studies of procedural learning in medicated schizophrenia patients using predictive saccade paradigms have consistently demonstrated hypometric predictive responses. Findings from antipsychotic-naive schizophrenia patients indicate fewer or no deficits. This pattern of findings suggests that antipsychotic medications might adversely affect frontostriatal systems supporting procedural learning on this task. The accuracy and latency of predictive saccades were assessed in 25 antipsychotic-naive first-episode sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 69 publications
4
18
0
1
Order By: Relevance
“…53 Such deficits might influence response to a D2 antagonist such that striatal function may be relatively normalized but frontal cortex may shift further into a state of hypofunction via local effects or changes in thalamic drive. Treatment-related DLPFC reduction is consistent with prior studies showing reduced spatial accuracy of predictive saccades after treatment in first-episode schizophrenia patients 12 and in chronically treated patients. 50,54,55 Measurement of saccade accuracy Notes: Two of the significant clusters from the analysis extended over multiple brain structures.…”
Section: Posttreatment Effectssupporting
confidence: 80%
See 2 more Smart Citations
“…53 Such deficits might influence response to a D2 antagonist such that striatal function may be relatively normalized but frontal cortex may shift further into a state of hypofunction via local effects or changes in thalamic drive. Treatment-related DLPFC reduction is consistent with prior studies showing reduced spatial accuracy of predictive saccades after treatment in first-episode schizophrenia patients 12 and in chronically treated patients. 50,54,55 Measurement of saccade accuracy Notes: Two of the significant clusters from the analysis extended over multiple brain structures.…”
Section: Posttreatment Effectssupporting
confidence: 80%
“…12 Functional imaging studies have not been conducted to identify the neural substrate of this treatment-emergent abnormality. Prior task-based imaging studies in first-episode patients have found treatment-emergent reductions in DLFPC and striatum activation, 10,22,23 so alterations to striatal and frontal systems may underlie the behavioral changes observed for predictive saccades after antipsychotic treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The double dissociation between medication type and task impairment makes it difficult to attribute the deficits to schizophrenia. The prospective study by Harris et al (2009) provides strong evidence that learning impairments are caused by antipsychotics. They tested procedural learning in antipsychotic-naïve firstepisode schizophrenia patients and found no impairments.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that learning mirror drawing that relies on the striatum is impaired in schizophrenia patients treated with risperidone (Scherer et al 2004). In a prospective study, Harris et al (2009) found that first-episode drug-naïve patients subsequently treated with risperidone became impaired on a predictive saccade task. Recently, Rémillard et al (2010) reported that risperidone does not impair the same procedural learning tasks as typical antipsychotics.…”
Section: Discussionmentioning
confidence: 98%